(untitled) (Mustansiria Dental Journal, 2005)
Confusion may exist in facing the problem of impressions for hypermobile mucosa specially when the problem is how to make this impression, various techniques have been advocated and the proper selection of one technique or another depends on available knowledge of functional and histologic anatomy for the development of impression procedure with a wide difference in the interpretation of the denture foundation. impression pressures have been thought to be a primary cause of tissue displacement and consequently a factor of denture instability. This study was carried out to compare 2 different impression techniques for anterior ilabby lower ridge, it has been concluded that more retention with better patient satisfaction were gained with lower dentures made using the window impression technique